Using Blogs as a Medium for Learning Feature Writing Skills - Handayani, Dina Fitria; Deswarni, Dini; Rahmah, Annisa Mutia (Postgraduate School, Universitas Negeri Padang, 2024)
Blog is a digital media many people use to express themselves and share information. In addition, blogs can be used as a medium for learning feature writing skills. This research is motivated by students' difficulties in generating story ideas, organizing stories, and balancing facts and narrative. This study aims to describe the use of learning media in the form of blogs in learning feature writing. This study is a qualitative research. The data collection techniques used were interviews, observations, and document studies on the results of students' feature writing. Based on the data analysis, it was obtained an overview of the skills in feature writing, 15 students got grades in the good category and 5 people got grades in the fair category.